MUI’s Fatwa as Non-State Economic Regulation: Maqasid al-Shari'ah and the Political Economy of Productive-Asset Zakat in Indonesia - Islami, Hayatul; Kurniawan, Cecep Soleh (Tuah Foundation, 2026)
Contemporary zakat studies have grown considerably, yet they rarely analyze fatwas as regulatory instruments that shape economic behavior in the absence of state enforcement. This article takes up that question through a socio-legal study of the 2024 fatwa of the Indonesian Ulama Council (Majelis Ulama Indonesia, MUI) on productive-asset zakat (al-mustaghallāt), issued under No. 05/Ijtima' Ulama/VIII/2024 at the MUI Fatwa Commission's Eighth National Ijtima'. Two questions guide the analysis: how does the fatwa's maqāṣid-based reasoning distinguish productive assets from their yields, and how does that distinction reshape middle-class asset management, MSME accounting, and national zakat governance? Drawing on qualitative content analysis of the fatwa text, classical fiqh sources, and interviews with drafting committee members, the article reports three findings. First, by anchoring the zakat obligation to income rather than to the underlying asset, the fatwa operationalizes ḥifẓ al-māl, al-namāʾ, maṣlaḥah, and tadāwul al-amwāl as a coherent economic rationale rather than as abstract objectives. Second, the ruling creates incentives for middle-class property owners and MSMEs to adopt sharīʿah-compliant income recording, which expands the administratively legible zakat base beyond traditionally captured wealth. Third, despite lacking statutory force, the fatwa produces fiscal effects comparable to state regulation through BAZNAS uptake and voluntary compliance among religiously motivated economic actors. These findings support a revised analytical framework in which non-state religious rulings are treated as active regulators within the political economy of Muslim-majority states, with direct implications for the design of complementary zakat policy, sharīʿah-based accounting standards for MSMEs, and comparative research on hybrid religious-state fiscal governance.